Anesthetic efficacies of intrapapillary injection in comparison to inferior alveolar nerve block for mandibular premolar extraction: a randomized clinical trial - Duangkamon Wongpang (2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. Objective: Intrapapillary injection (IPI) has been suggested to improve pulpal anesthesia of mandibular teeth and to avoid complications from inferior alveolar nerve block (IANB). This study aimed to determine and compare clinical efficacies and prostaglandin E2 (PGE2) levels between IPI and IANB. Materials and methods: IANB was randomly selected for mandibular premolar anesthesia on one side of 40 patients, whereas IPI was locally administered to the contralateral premolar. Pulpal anesthesia, pain during injection and extraction, patients’ satisfaction, and complications were assessed from 30 patients. Gingival crevicular fluid from ten patients was collected for PGE2 quantification by ELISA. Results: Of 30 patients, 18 preferred IPI after injection due to significantly faster mean onset of pulpal anesthesia (p < 0.001) and lower mean score of injection pain (p = 0.017) than IANB, but 21 preferred IANB instead after extraction due to less postoperative pain, consistent with the significantly lower median PGE2 level on the IANB side than that on the IPI at 30 min (p = 0.047). However, there was no difference in the mean satisfaction score between the two techniques. Ulcerated epithelium and sloughing tissues were found at the IPI site in some patients with complete healing within 2 weeks. Conclusions: The anesthetic efficacies of IPI for mandibular premolar extraction are comparable to those of IANB. However, postoperative pain and local complications at the IPI site should be considered. Clinical relevance: IPI may be used for dental procedures that require only a short anesthetic duration to avoid failure of pulpal anesthesia, complications, and discomfort from IANB.